L-Band GHz Femtosecond Passively Harmonic Mode-Locked Er-Doped Fiber Laser Based on Nonlinear Polarization Rotation - Yuanda Ling; Qianqian Huang; Chuanhang Zou; Zhikun Xing; Zhijun Yan; Chang Zhao; Kaiming Zhou; Lin Zhang; Chengbo Mou (IEEE Photonics Journal)
Via using an L-band optimized in-fiber polarizing grating device, a GHz L-band femtosecond passively harmonic mode-locked Er-doped fiber laser based on nonlinear polarization rotation is first demonstrated. In total, 4.22 GHz pulses with the duration of 810 fs and super-mode suppression ratio (SMSR) of 32 dB are obtained under the pump power of 712 mW corresponding to 215th harmonic order. The central wavelength of 4.22 GHz pulses is 1581.7 nm with 10.1 nm 3 dB bandwidth. Furthermore, under this fixed pump power, higher harmonic orders can also be attained by rotating the polarization controllers properly. The highest repetition rate we obtained is 7.41 GHz with the SMSR of 20.7 dB.